E-Credentials, Online Credential Request for King’s College of the Philippine - Genaro Anasan; Kenneth Basquial; Mel Cadley; Mecie Camacho; Chysis Pascual; Myriel Nginsayan (Southeast Asian Journal of Science and Technology, 2025)
The King’s College e-Credentials System is a capstone project designed to digitize the manualacademic document request process at King's College of the Philippines. Developed using the Rapid ApplicationDevelopment (RAD) methodology and technologies like PHP and MySQL, the system introduces a web-basedplatform to address inefficiencies such as long queues. The platform features a role-based architecture for Students,Registrar, Accounting, and Super Admin users. Key functionalities enable students to submit requests, pay online viaPaymongo, and track statuses in real-time, while administrators manage, verify, and process documents through acentralized dashboard. The system underwent rigorous testing, including Unit and User Acceptance Testing (UAT).Evaluation using a 5-point Likert scale based on the Post-Study System Usability Questionnaire (PSSUQ) yielded anoverall weighted mean of 4.52, interpreted as "Strongly Agree." This confirms high user satisfaction acrossfunctionality, usability, security, and reliability. In conclusion, the E-Credentials System successfully modernizesrecord management by reducing administrative burdens, enhancing security, and providing a more accessible andefficient service for students, establishing a sustainable digital foundation for the institution.